Using Smartphones to Prevent Cross-Functional Team Knowledge Hiding: The Impact of Openness & Neuroticism - Ton, Anh Don; Hammerl, Laszlo; Szabó-Szentgróti, Gábor (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The study examines the behaviour of two characteristic traits on knowledge retention, mediated using modern smartphone usage in the corporate environment of cross-functional teams. For the investigation, a self-made model was applied that associates the personality, focusing on the traits of neuroticism and openness towards new concepts and statistically evaluates the effect of increased technological usage. A dataset of 101 individuals working in cross-functional teams was used to test the model. A total of four main hypotheses were developed and statistically tested. Exalted presence of openness towards new experiences was evaluated as a critical factor leading to decreasing knowledge retention. Furthermore, although it was deducted, that neuroticism could not be verified as a knowledge limiting factor in the applied model, smartphone usage could drastically reduce its potentially dangerous factors by using efficient and short communication channels, reaffirmation and commendation by higher-ups and colleagues alike to bolster the missing self-esteem and self-consciousness of neurotic individuals. In contrast, openness was not connected significantly to deliberate knowledge hiding, as individuals incorporating this trait presumably tend to use technological tools of all kinds inherently due to their eagerness to experiment.